Impacts of cool transportation in Nigeria: Midpoint analysis - Yamauchi, Futoshi; Dauda, Bawa; Balana, Bedru; Edeh, Hyacinth O.; Shi, Weilun (International Food Policy Research Institute, 2024)
A randomized controlled trial was introduced to see impacts of cool transportation that connects three vegetable markets in northeast and two large demand centers in southern regions of Nigeria. This note summarizes the findings from the midpoint analysis. First, the impact of cool transportation is large and statistically significant. Sales price, revenue and profit significantly increase for marketers. Second, impacts on sales price are quantitatively large, and a larger portion of sales price increase is attributed to refrigeration, that is, quality preservation through cooling. About 70% of the increase comes from cooling; only 30% from transportation. Third, impacts on revenue and profit, relative to non-cool transportation, are also quantitatively large. In particular, the analysis shows a large proportional increase in profit.